2010
DOI: 10.1371/journal.pgen.1001110
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Genetic Perturbations to MCM2-7 Expression and Subcellular Distribution Reveal Exquisite Sensitivity of Mice to DNA Replication Stress

Abstract: Mutations causing replication stress can lead to genomic instability (GIN). In vitro studies have shown that drastic depletion of the MCM2-7 DNA replication licensing factors, which form the replicative helicase, can cause GIN and cell proliferation defects that are exacerbated under conditions of replication stress. To explore the effects of incrementally attenuated replication licensing in whole animals, we generated and analyzed the phenotypes of mice that were hemizygous for Mcm2, 3, 4, 6, and 7 null allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 43 publications
8
119
1
Order By: Relevance
“…To examine genomic copy number changes, we performed array comparative genomic hybridization (aCGH) on 12 Chaos3 tumors (nine Chaos3 mammary and three nonmammary), and two MMTVNeu mammary tumors. Chaos3 nonmammary tumors can be obtained by genetic perturbations or altering the strain background (Chuang et al 2010;Kawabata et al 2011b). Strikingly, the Chaos3 tumors exhibited highly recurrent CNAs in a small number of regions.…”
Section: Resultsmentioning
confidence: 99%
“…To examine genomic copy number changes, we performed array comparative genomic hybridization (aCGH) on 12 Chaos3 tumors (nine Chaos3 mammary and three nonmammary), and two MMTVNeu mammary tumors. Chaos3 nonmammary tumors can be obtained by genetic perturbations or altering the strain background (Chuang et al 2010;Kawabata et al 2011b). Strikingly, the Chaos3 tumors exhibited highly recurrent CNAs in a small number of regions.…”
Section: Resultsmentioning
confidence: 99%
“…It is presently unclear whether the increase in MCM protein levels itself could result in some of the phenotypes associated with MCM-BP depletion, as the role of the soluble pool of MCM proteins is currently unknown. However, it is interesting to note that a recent study in mice has shown that seemingly small decreases in MCM protein levels can affect MCM localization and result in replication stress (Chuang et al, 2010). It remains to be determined whether increases in MCM levels also have detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the observation that the capsule appears to be thin adjacent to the regions of infiltration, further suggesting that over time the rate of infiltration exceeds the ability of the capsule to self-renew. Depletion of MCMs has been proposed to lead to stem cell defects in mice (7,18), with lower MCM2 levels associated with reduced numbers of stem cells in the subventricular zone, skeletal muscle, and intestinal crypts in adult mice. Similarly, the relatively specific impingement of the MCM4 defect on adrenal function may be a consequence of its effect on the growth of these mesenchymal stem/progenitor cells and their differentiation into steroidogenic cells.…”
Section: Discussionmentioning
confidence: 99%